Neuropsychological outcomes after thalamic deep brain stimulation for essential tremor. (November 2021) - Dhima, Kaltra; Biars, Julia; Kondylis, Efstathios; Nagel, Sean; Yu, Xin Xin; Floden, Darlene P.
Abstract: Introduction: Non-motor DBS outcomes have received little attention in ET relative to PD. This study examines neuropsychological outcomes in ET following thalamic VIM DBS. Methods: Fifty patients completed neuropsychological evaluations preoperatively and approximately seven months postoperatively. Cognition and mood changes were analyzed at the group level and individual level. Additional associations with treatment, disease, and demographic characteristics were assessed. Results: Significant cognitive decline was not observed at the group level. At the individual level, 46% of patients demonstrated at least subtle overall cognitive decline (≥1SD on at least one test within at least two domains). Mild decline (≥1SD) was seen in 10%–29.17% of patients on individual tests across all cognitive domains, with highest rates in verbal memory. Substantial cognitive decline (≥2SD) occurred in less than 9% of the sample across all tests. Factors related to cognitive decline included higher DBS parameter settings, older age of ET onset, intracranial complications, and inability to reduce ET medications postoperatively. Depression and anxiety did not change when accounting for questionnaire items that could be falsely elevated by tremor. Conclusion: Substantial cognitive decline after VIM DBS is rare in patients with ET. However, subtle decrements can occur across cognitive domains and particularly in verbal memory. DBS parameter settings may relate to cognitive decline. Further research is needed to better understand possible associations with electrode lateralization and other variables that could also relate to disease progression and test-retest effects. Symptoms of depression and anxiety remain stable. Highlights: DBS for ET appears generally safe from a neuropsychological standpoint. Slight cognitive decline is possible, especially in aspects of verbal memory. About half of patients may experience subtle decline in overall cognition. Stimulation parameters may relate to subtle cognitive decline. Symptoms of depression and anxiety remain generally stable after surgery.